Climate Change Realities, Impacts Over Ice Cap, Sea Level and Risks - Raj Singh, Bharat (IntechOpen, 2013)
The Earth is the only planet in our solar system that supports life. The complex process of evolution occurred on Earth only because of some unique environmental conditions that were present: water, an oxygen-rich atmosphere, and a suitable surface temperature. Climate change refers to a statistically significant variation in either the mean state of the climate or in its variability, persisting for an extended period (typically decades or longer). Thus, it requires field of attention towards reduction in the rise in atmospheric temperature, by controlling emitted greenhouse gases into the atmosphere in order to preserve natural resources and by introducing new technologies on alternative fuels. This book presents the fundamental effect on the origin of climate change, impacts over ice cap, melting of Arctic ice, rise in sea level and related technologies that can be implemented to cultivate our land for agriculture, growing forestation to reduce the impact of temperature rise and disaster on human being as well as on other livelihood. This also need to strive for novel policies that world leader should adopt.